The Najd Arda as a starting point for creativity in Saudi plastic painting (Al-Academy, 2023)
The popular heritage is an important part of the culture, as it provides a fertile ground for the artistic work, including the customs and traditions it contains that can be inspired in the construction of artworks. Therefore, the Saudi artist seeks, through his artistic approach to the Najd show, to find a springboard for creativity linked to his national identity, relying on adherence to his identity and culture in facing the challenges resulting from development and openness to other cultures.The Najd Ardah is one of the important elements of the cultural heritage that has been associated with the conscience of the artist and the Saudi man throughout the ages. It was an important, rich and visually exciting subject that could be relied upon in his artistic formations. Accordingly, the research problem is determined in the following question: Is it possible to find a springboard for creativity in Saudi plastic photography by drawing inspiration from the Najdi Arda for the artist to deal with in his plastic production?The research aims to identify one of the manifestations of Saudi culture represented in the Najdi Arda and to find a springboard for creativity in Saudi plastic photography by drawing inspiration from the Najdi Arda to be dealt with by the artist in his plastic production. The researcher followed the descriptive analytical approach in tracking the literature related to the Najdi Arda and analyzing the artworks related to it. The Najd Ardah is an important element that the artist uses to express in his artwork in a contemporary artistic style that aims to convey an idea or concept through the image, either in a reduced or abstract way. Al-Ardah Al-Najdiyya with its vocabulary is a strong influencer in presenting topics and stimulating the artist towards the development of the new in the way of presentation, style and technique of the artwork